Influência da luz e da temperatura na germinação de Dipteryx alata Vog - Silva, Jean Carlos Siqueira (2016)
To evaluate the influence of light and temperature on germination of Dipteryx alata Vog seeds, mature fruits were collected from several matrices in the municipality of Rondo nópolis - MT. The treatments were maintained in germination chambers equipped with white fluorescent lamps, in a 2 × 5 factorial arrangement, consisting of two light condi tions, with photoperiod of 10 h light and dark, distributed in five temperature regimes, four (25, 30, 35 and 40 ° C) and an alternating temperature (20-35 ° C) using a completely randomized model with four replicates of 12 seeds. Daily counts were performed up to the 14th day after sowing, to evaluate the germination percentage, the IVG rate index and the mean TM germination time. It is concluded that the seeds of Dipteryx alata are neutral photoblasts and the constant temperature of 35 ° C is the most suitable germination con dition, but in the other temperatures below 35 ° C the species had negative photoblastic characteristics.